Mandela Yoga: a community case study for a post-incarceration reentry service for men of color in recovery - Gawande, Richa; Rosario, Felipe Kalatauma; Santiago, Carlos; Thomas, Jeffrey; Naganuma-Carreras, Julia; Blot, Tori; Aviles, Keyona; Gardiner, Paula; Schuman-Olivier, Zev (Frontiers in Public Health, 2025)
BackgroundDisparities in substance use treatment access and outcomes between communities with racially, economically, linguistically, and mentally/physically marginalized identities and more privileged populations are staggering. Communities of color lack access to culturally resonant treatment options that incorporate the role of racial oppression, address the chronic effects of stress on the nervous system, provide culturally-and linguistically-matched community support in substance use recovery, and contend with social determinants of health. Mandela Yoga, a community-based peer-led mindfulness intervention, was created to address disparities in health and substance use treatment access among communities of color. Mandela Yoga was co-developed by Black and Brown yoga teachers, therapists, and community leaders with lived experienced of recovery, incarceration, chronic illness, and racism. A Mandela Yoga community reentry services implementation was funded by a Massachusetts Department of Public Health Bureau of Substance Abuse Services grant for overdose risk reduction for people recently released from incarceration.ObjectivesIn this community case study, we present a qualitative analysis of a 12-week Mandela Yoga implementation as part of a Federally Qualified Health Center reentry program focused on post-incarceration opioid overdose risk reduction among men of color. Through a community-based participatory approach, we feature the voices and lived experiences of the peer facilitator and a reentry services participant, who are co-authors and shaped the qualitative analysis.MethodsWe documented attendance and conducted interviews with the Mandela Yoga peer facilitator and one participant. Together we conducted a thematic analysis of the interviews to explore key elements that most impacted recovery and healing.ResultsWe report on the delivery and attendance of the implementation. We present excerpts illustrating four key themes that emerged from the interviews: (1) Breath and Mind–Body Connection Leads to Presence; (2) Consistency; (3) Peer Connection; (4) Agency and Positive Action.DiscussionWe explore how Mandela Yoga may build recovery capital and the mechanisms by which it may support healing from addiction and trauma in communities of color. We discuss study limitations and considerations for future implementations.ConclusionMandela Yoga shows promise as a mind–body-community intervention for communities of color in recovery and post-incarceration.